TELAAH KRITIS PUTUSAN MAHKAMAH KONSTITUSI DAN DAMPAKNYA TERHADAP PEMBERANTASAN KORUPSI - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Abstract Issue about unlaqUI theory is brought back by the Decision of Constitutional Court 0031PUU-IV120015 which staled that Corruption Combating Act. Article 2, Paragraph I. concerning the material unlimfid is not binding. This writing tries to discuss the Constitutional Court's basic considerations, the unlahfid theory and the impact of the rule in continuing corruption.